Prenatal diagnosis of chromosomic defects in Costa Rica - Castro Volio, Isabel (2004)
This is an historical overview of prenatal cytogenetic diagnosis in Costa Rica. It started in 1984 at the Institute for Health Research of the University of Costa Rica. This is the only fetal cytogenetic diagnosis facility in the country and serves social security as well as private patients. Perinatologists send amniotic fluid and fetal blood samples from high risk pregnancies, mainly due to abnormal ultrasound assessment, sonographic markers of aneuploidy and advanced maternal age. Second and third trimester diagnosis allows the development of coping strategies for the families of affected fetuses, since pregnancy interruption is not permitted. Normal fetal cytogenetic results provide reassurance to the parents.